2017
DOI: 10.1186/s12885-017-3264-y
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib treatment of poor prognosis mesenchymal-type primary colon cancer: a proof-of-concept study in the preoperative window period (ImPACCT)

Abstract: BackgroundThe identification of four Consensus Molecular Subtypes (CMS1–4) of colorectal cancer forms a new paradigm for the design and evaluation of subtype-directed therapeutic strategies. The most aggressive subtype - CMS4 - has the highest chance of disease recurrence. Novel adjuvant therapies for patients with CMS4 tumours are therefore urgently needed. CMS4 tumours are characterized by expression of mesenchymal and stem-like genes. Previous pre-clinical work has shown that targeting Platelet-Derived Grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Another activated signalling pathway is the PDGFR pathway which can be targeted by the imatinib anticancer drug. The ongoing ImPACCT clinical trial investigates the efficacy of the drug in patients with colon cancer characterised as CMS4, described in Ubink et al …”
Section: The Biological Mechanism Of the Tumour Stroma In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another activated signalling pathway is the PDGFR pathway which can be targeted by the imatinib anticancer drug. The ongoing ImPACCT clinical trial investigates the efficacy of the drug in patients with colon cancer characterised as CMS4, described in Ubink et al …”
Section: The Biological Mechanism Of the Tumour Stroma In Colon Cancermentioning
confidence: 99%
“…49 For an extensive summary of TGF-b targeting drugs, see the review by Colak et al 50 Another activated signalling pathway is the PDGFR pathway which can be targeted by the imatinib anticancer drug. The ongoing ImPACCT clinical trial investigates the efficacy of the drug in patients with colon cancer characterised as CMS4, described in Ubink et al 51 Therapeutically targeting CAFs can also promote anti-tumour response, and it could be used in combination with standard therapy in order to target both CAFs and cancer cells. For instance, sibrotuzumab is an antibody that inactivates the CAF marker FAP.…”
Section: T a R G E T I N G T H E S T R O M A L C O M P A R T M E N Tmentioning
confidence: 99%
“…Therefore, studies are underway to identify targeted therapeutic options beneficial for the CMS4 subtype (rectal adenocarcinoma NCT02688712, phase II and tyrosine kinase inhibitor Fig. 2 Survival of patients with CRC (N = 201) stratified by tumourstroma ratio (a) and by CDX2 status in the stroma-low subgroup (b; N = 105) and the stroma-high subgroup (c; N = 96) (log-rank test, pairwise comparisons controlling for false discovery rate using the Benjamini-Hochberg procedure and unadjusted p value for interaction between tumour-stroma ratio and CDX2 status in disease-free survival and overall survival) [18]). Once a beneficial treatment for this subgroup will be available, an easy to use stratification method will be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet derived growth factor (PDGF) signaling pathway promotes processes of cancer aggressiveness as epithelial mesenchymal transition (EMT), tumor proliferation, growth and progression, angiogenesis, inhibition of apoptosis, recurrence and metastatic dissemination via the activation of various signaling pathway as PI3K/AKT and RAS/MAPK signaling pathways [3][4][5]. Platelet-derived growth factor receptors (PDGFR) and their ligands were reported as highly expressed in consensus molecular subtypes 4 (CMS4) colon tumors and identified as potential therapeutic targets for this subtype [6]. Dysregulation of PDGFR alpha (PDGFRα), one of receptors tyrosine kinase (RTK), has been reported in a broad range of cancer including glioblastoma, breast cancer, hepatocellular carcinomas, pancreatic cancer, and ovarian cancer [4,[7][8][9], either by protein overexpression or by the effect of mutations and chromosomal rearrangements.…”
mentioning
confidence: 99%
“…Moreover, this receptor has been approved by the Food and Drug Administration as therapeutic target for the treatment of patients with gastrointestinal stromal tumors (GISTs) (https ://www.brimr .org/PKI/ PKIs.htm). It was shown that Imatinib (PDGFRα inhibitor) can reduce the aggressive phenotype of CMS4 class colorectal tumors [6,10].…”
mentioning
confidence: 99%